Strategi Komunikasi Periklanan Produk Yamaha NMAX Turbo 2024 - Rafiuddin Akil; Salsabila Andi Akil; Alamsyah; Ayi Muhiban; Yanti Setianti (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This study aims to analyze the advertising communication strategy for the Yamaha NMAX Turbo 2024, Yamaha's latest product positioned as a premium scooter with turbocharged technology. Amid the fierce competition in the automotive industry, Yamaha needs to design an innovative and effective advertising campaign to increase brand awareness and consumer purchase intention. The objective of this research is to identify key elements in Yamaha’s advertising communication strategy, evaluate its effectiveness, and understand its impact on consumer perceptions and marketing goals. This research employs a descriptive approach with qualitative and quantitative analysis, combining consumer surveys, in-depth interviews, and ad content analysis. The findings show that the effectiveness of the ads, social media engagement, and brand awareness have significant effects on consumer purchase intention, especially among Gen Z. The effectiveness of the ads proved to be the most influential factor, followed by brand awareness and social media engagement. Consumers who responded to Yamaha NMAX Turbo ads through social media tended to have a positive perception of the product's innovations and advanced features. Additionally, the survey indicated that consumers actively engaged with social media campaigns were more motivated to make a purchase. The integrated communication strategy, utilizing various digital platforms such as social media, websites, and television ads, has been proven to increase purchase intention and strengthen positive perceptions of the Yamaha NMAX Turbo. Based on these findings, it is recommended that Yamaha continue to develop creative ad content, enhance social media engagement, and expand brand awareness campaigns through collaborations with automotive influencers. This strategy is expected to solidify Yamaha NMAX Turbo's position in the Indonesian automotive market.